2008
DOI: 10.1080/10717540802321826
|View full text |Cite
|
Sign up to set email alerts
|

Transport of Surface Engineered Polyamidoamine (PAMAM) Dendrimers Across IPEC-J2 Cell Monolayers

Abstract: The aim of our study was to prepare arginine-and ornithineconjugated Polyamidoamine (PAMAM) dendrimers and study their permeability across IPEC-J2 cell monolayers, a new intestinal cell line model for drug absorption studies. Arginine and ornithine were conjugated to the amine terminals of the PAMAM G4 dendrimers by Fmoc synthesis. The apical-to-basolateral (AB) and basolateral-to-apical (BA) apparent permeability coefficients (P app ) for the PAMAM dendrimers increased by conjugating the dendrimers with both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 45 publications
(50 reference statements)
0
20
0
Order By: Relevance
“…54,55 In both cell lines, there was no significant difference in cytotoxicity between polyamine-conjugated dendrimer and native dendrimers. Furthermore, a concentration and timedependent enhancement in permeability was observed from apical to the basolateral side for the polyamine conjugated PAMAM dendrimers.…”
Section: Toxicity Of Pamam Dendrimers In the Context Of Oral Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…54,55 In both cell lines, there was no significant difference in cytotoxicity between polyamine-conjugated dendrimer and native dendrimers. Furthermore, a concentration and timedependent enhancement in permeability was observed from apical to the basolateral side for the polyamine conjugated PAMAM dendrimers.…”
Section: Toxicity Of Pamam Dendrimers In the Context Of Oral Deliverymentioning
confidence: 99%
“…Furthermore, a concentration and timedependent enhancement in permeability was observed from apical to the basolateral side for the polyamine conjugated PAMAM dendrimers. 54,55 Another proven strategy to improve biocompatibility and pharmacokinetics of polymeric drug carriers in vivo is PEGylation. PEGylation of anionic dendrimers G3.5-COOH and G4.5-COOH with PEG 750 kDa did not significantly alter cytotoxicity up to a concentration of 0.1 mM.…”
Section: Toxicity Of Pamam Dendrimers In the Context Of Oral Deliverymentioning
confidence: 99%
“…A drug transport permeability study showed that IPEC-J2 cells form a tighter monolayer compared to Caco-2 cells (Pisal et al 2008 ). On the other hand, Caco-2 and T84 cells produce a more pronounced mucus layer compared to IPEC-J2 cells (Navabi et al 2013 ).…”
Section: Relevance To Human In Vivo Situationmentioning
confidence: 99%
“…The intestinal epithelium of pigs performs a critical role in nutrient absorption and serves as a barrier, limiting the permeability of toxic substances (Zhao et al, ). In addition, the epithelial cell barrier protects the mucous membrane of the gastrointestinal tract (Pisal, Yellepeddi, Kumar, & Palakurthi, ). The tight intracellular junction proteins lie between the epithelial cells, which restrict the absorption of drugs and prevent the flow of possible antigens and pathogens from the lumen to the sub‐mucosa (De Magistris, ; Pisal et al, ).…”
Section: Discussionmentioning
confidence: 99%